A comparison of student and faculty attitudes on the use of Zoom, a video conferencing platform: A mixed-methods study. (July 2021) - Vandenberg, Shannon; Magnuson, Morgan
Abstract: Aim: The COVID-19 pandemic has generated opportunities and challenges for nursing education, with many nursing programs transitioning in-person courses to online delivery with varying degrees of success. This study aimed to compare the attitudes of baccalaureate nursing students and nursing faculty members towards the use of Zoom for nursing education in Alberta, Canada. Design: A mixed-methods design was used to measure student and faculty attitudes. Methods: Data were collected using a Likert-scale survey with the opportunity to share additional perceptions in the form of qualitative data. Quantitative data underwent descriptive analysis as well as inferential analysis comparing results from both groups. A thematic analysis was conducted for qualitative data. Results: Most student and faculty participants favour in-person learning approaches to online platforms. Students' attitudes toward online practice experiences were overwhelmingly negative, citing concerns with lack of relational practice and skill development. Achievements and barriers were also identified with online learning. Conclusions: With an uncertain future in nursing education, opportunities exist to examine current nursing education program delivery and thoughtfully augment in-person learning approaches with online methods.